PROTECTION OF WOMEN'S AND CHILDREN'S RIGHTS BASED ON SYSTEM INTERCONNECTION: A New Paradigm of Execution of Women and Children's Rights after Divorce - Amran Suadi (Pusat Strategi Kebijakan Hukum dan Peradilan Mahkamah Agung RI, 2022)
The implementation of post-divorce decisions in the religious court demands great attention because the system for implementing decisions in divorce cases still needs to be stronger. The cost of executing the decision is not commensurate with the nominal (the ex-husband must pay “the obligation” to his ex-wife). As a result, court decisions become “useless”, which are only authoritative in writing but weak in implementation. Through this paper, the author wants to explain a new concept related to the fulfillment of the rights of women and children after divorce based on an interconnected system so that post-divorce women and children are guaranteed their fulfillment of rights without going through the process of execution in court. This research is normative research through a statutory approach and a conceptual approach. This research shows that ensuring the women's and children's rights fulfillment requires an interconnected system. Courts must involve non-judicial institutions in an integrated manner following their respective authorities. This new framework makes institutions outside the judiciary as external partners in implementing single identity-based court decisions.